THA DEVELOPMENT OF AGRARIAN LAW - maisa maisa; Haerani Husainy (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
In Indonesia, agrarian law gets a place of attention for all circles, this is because of various kinds of problems that are directly related to the location of the Indonesian state which is an agrarian country. So that the eyes of the world are fixed on how to take part in the benefits of natural resources owned by Indonesia. So it is necessary to strengthen laws that are directly related to agrarian in Indonesia, the development of agrarian law is undeniable that the progress of the times has changed the pattern of handling conflicts that often occur which involve the community as the aggrieved party. Therefore, the development of agrarian law needs to be a concern, especially the government to be able to provide legal certainty and it is also hoped that there will be a concept based on social justice in handling agrarian affairs in Indonesia. This research was conducted using a normative juridical approach that focuses on the study of literature and legislation related to the development of agrarian law in realizing justice in the agrarian sector in Indonesia.